Improved spectrophotometric method for nitrite determination in processed foods and dietary exposure assessment for Korean children and adolescents. (15th January 2022) - Lim, Ho Soo; Choi, Euna; Lee, Sang Jin; Nam, Hye Seon; Lee, Jong Kwon
Highlights: An improved method for nitrite analysis was established and validated. Nitrite contents in processed food products were analyzed by applying the method. The daily intake of nitrite for Korean children and adolescents was estimated. The nitrite intakes were much lower than the ADI of 0.07 mg/kg bw/day for all groups. Abstract: A spectrophotometric method based on diazo-coupling reaction for nitrite analysis was established and validated, including inter-laboratory validation, linearity, accuracy, precision, the limit of detection (LOD) and limit of quantification (LOQ). The time-saving and high-recovery method was established by examining the filtration step, colorimetric process and concentration range of the calibration curve. This method showed good linearity ( r 2  > 0.999) in the range of 0.025–1.0 μg/mL. The three-level recoveries were between 86.7% and 108.6%, with the coefficient of variation (CV) below 5.8%. Mean nitrite concentration ranges in processed foods were ND–33.47 mg/kg. The mean nitrite intake was 0.8% of the Acceptable Daily Intake (ADI, 0.07 mg/kg bw/day) for all children and adolescents and 2.8% for the consumer group. The major contributors for all subjects and consumers were ham, sausage and bacon. These results indicated that the improved method was suitable for analyzing nitrite in processed foods and the nitrite exposure levels were safe.